Pertumbuhan Dan Serapan Kalium Bibit Kelapa Sawit (Elaeis guineensis jacq.) Dimain-Nurserydengan Efeksisa Pemupukan Pada Beberapa Medium Tumbuh - Feryono '; rmaini '; Arnis En Yulia (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
This research aimed to determine the response of the growth of oil palm seedlings and how much kalium can absorb by oil palm seedlings on different organic fertilizersources with some planting medium. This research has done in experimental plantation Agriculture Faculty, University of Riau from October until February 2013. This research used completely randomized design non factorial  with the combination of some organic fertilizer and some medium as the treatment. The organic fertilizer include: bird’s manure, sludge fertilizer, liquid organic fertilizer and without fertilizer as control. Some medium include: PMK soil, peat soil and mix of PMK and peat soil 1:1. The result showed that the best treatment was the combination of residue effect of liquid organic fertilizer in PMK and Peat soil medium because its can be inclined grow up fresh seedling weight, seedling dry weight, the quality of seedling’s indexand the absorb of kalium. Key words: Oil Palm, Organic fertilizer, PMK Soil and Peat Soil.